The Existing Interventions to Promote Self-Care and Self-Monitoring Preventing Hypertension Among Thai Risk People: A Scoping Review - Banharak S; Potempa K; Limpawattana P; Pamungkas RA; Mahikul W; Jeamjitvibool T; Karaket A; Siriprathum S; Ransinyo K (Vascular Health and Risk Management)
Samoraphop Banharak,1 Kathleen Potempa,2 Panita Limpawattana,3 Rian Adi Pamungkas,4 Wiriya Mahikul,5 Thanakrit Jeamjitvibool,6 Anusorn Karaket,7 Sittipong Siriprathum,8 Khanisorn Ransinyo1 1Department of Gerontological Nursing, Faculty of Nursing, Khon Kaen University, Khon Kaen, Thailand; 2Department of Systems, Populations, and Leadership, School of Nursing, University of Michigan, Ann Arbor, MI, USA; 3Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 4Department of Nursing, Faculty of Health Sciences, Universitas Esa Unggul Jakarta, Jakarta, Indonesia; 5Department of Medicine, Princess Srisavangavadhana Faculty of Medicine, Chulabhorn Royal Academy, Bangkok, Thailand; 6Department of Adult and Geriatric Nursing, Princess Agrarajakumari College of Nursing, Chulabhorn Royal Academy, Bangkok, Thailand; 7Nursing Department, Rasi Salai Hospital, Rasi Salai, Sisaket, Thailand; 8Nursing Department, Chumphae Hospital, Chumphae, Khon Kaen, ThailandCorrespondence: Samoraphop Banharak, Email sbanharak@kku.ac.thAbstract: Hypertension affects one-third of the worldwide adult population and is a major contributor to premature mortality in Thailand. However, hypertension is mainly preventable, highlighting the need for effective prevention strategies to mitigate this critical health concern. This scoping review aimed to identify existing knowledge gaps and provide a comprehensive understanding of hypertension prevention interventions. Keywords were identified, and an unrestricted search for empirical studies was conducted until December 20, 2024. The search strategy encompassed 11 databases. Ultimately, studies focusing on preventive interventions targeting the Thai population at risk of hypertension were included in this review. Finally, we included 41 studies: 35 in community settings, two in hospital clinics, and four in Buddhist temples. The total number of participants was 16,401, ranging from 32 to 4,786, aged between 18 and 74. Research designs comprised 32 quasi-experimental studies, seven randomized controlled trials, one action research, and one research and development. Researchers primarily delivered interventions. The interventions focused on hypertension monitoring, knowledge promotion, health behavior modification, social support, and counseling, emphasizing preventive behaviors, nutrition promotion, and disease awareness. Researchers commonly took outcome measurements before and 12 weeks after intervention. Manuals, logbooks, and lectures with presentation slides were the primary platforms. Finally, knowledge, behaviors, and biomarkers were the most frequently assessed outcomes. This scoping review provided recommendations that future research should expand intervention strategies, emphasize biomarkers, adopt modern delivery methods like AI chatbots and mobile apps, and include follow-ups beyond 12 weeks to ensure lasting impact.Keywords: hypertension, intervention, review, self-care, self-management, self-monitoring